Optimal designs with a single two-level factor and n autocorrelated observations - Angelis L.; Bora-Senta E.; Moyssiadis C. (Utilitas Mathematica, 1997)
The problem of finding an optimal design with a single two-level factor and n observations, under the presence of correlation between errors, is considered. Assuming errors following a first order autoregressive model, the exact D- and A- optimal designs for the distinct cases of positive and negative correlation were found and their optimality was proved explicitly.